2013
DOI: 10.1371/journal.pone.0066607
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Lipocalin-2 and Retinol-Binding Protein 4 Are Associated with Intima-Media Thickness and Subclinical Atherosclerosis in Patients with Type 2 Diabetes

Abstract: BackgroundThe lipocalin family proteins, including lipocalin-2 and retinol-binding protein 4 (RBP4), are adipokines closely associated with obesity-related metabolic disorders. In this study, we evaluated the association of serum lipocalin-2 and RBP4 with intima-media thickness (IMT) and subclinical atherosclerosis in type 2 diabetic patients.Methods and ResultsSerum levels of lipocalin-2 and RBP4 were measured in 284 type 2 diabetic patients. Subclinical atherosclerosis was assessed by IMT at carotid, femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 36 publications
(43 reference statements)
2
46
0
Order By: Relevance
“…Elevated LCN2 levels have been found to be associated with several markers of CVD, such as intima-media thickness of arteries and the degree of severity. 10,13 In addition to its circulating levels, plaque levels of LCN2 tended to be higher when intraplaque hemorrhage or luminal thrombus was present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated LCN2 levels have been found to be associated with several markers of CVD, such as intima-media thickness of arteries and the degree of severity. 10,13 In addition to its circulating levels, plaque levels of LCN2 tended to be higher when intraplaque hemorrhage or luminal thrombus was present.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The association between LCN2 and presence and severity of atherosclerosis was confirmed in cross-sectional study. 10 However, prospective studies addressing the cause-effect relationship between LCN2 and CVD are still lacking. In the present study, we investigated the development of CVD events in relation to the baseline LCN2 levels in a population-based cohort recruited from the Shanghai Diabetes Study.…”
mentioning
confidence: 99%
“…[26][27][28][29] Moreover, elevated circulating NGAL concentrations predict adverse cardiovascular events in patients. 29,30 We and others, have previously showed that Lcn2/NGAL is a direct target gene of the aldosterone/MR signaling pathway in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Cabré et al (19) observed that RBP4 would increase in patients with T2DM complicated with coronary heart diseases, and that if levels of RBP4 increased by 1/4, the risk of cardiovascular diseases would increase by 2.5 times. A recent study (20) demonstrated that the levels of RBP4 had already increased in the early stages of the development of T2DM complicated with atherosclerosis. In the present study, RBP4 was positively correlated with TG, LDL-c, FINS, HOMA-IR, PFM, AIP, NF-κB and SBP, and negatively correlated with HDL-c following correlation analysis.…”
Section: Discussionmentioning
confidence: 99%